TAX REVENUE MOBILIZATION AND STATE BUDGET SUSTAINABILITY: EMPIRICAL EVIDENCE FROM UZBEKISTAN (2020–2024) - Mardonov Akromjon Nusrat ogli (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. The sustainability of public finances largely depends on the effectiveness of tax revenue mobilization and fiscal management. In developing economies, taxation represents the primary source of government revenue and serves as a fundamental instrument for financing public expenditures, maintaining macroeconomic stability, and promoting economic development. This study examines the impact of tax revenues on state budget sustainability in Uzbekistan during the period 2020–2024. The research employs a mixed-method approach combining statistical analysis, comparative analysis, and institutional assessment. The findings reveal that tax revenues consistently accounted for more than 80 percent of total state budget revenues, indicating a high degree of fiscal dependence on taxation. The analysis further demonstrates that recent tax reforms, improvements in tax administration, and the digitalization of tax processes have contributed significantly to revenue growth and fiscal stability. The study concludes that efficient tax administration, expansion of the tax base, and continued modernization of fiscal institutions are essential for ensuring long-term budget sustainability and sustainable economic growth.